Clonal versus non-clonal milkweeds (Asclepias spp.) respond differently to stem damage, affecting oviposition by monarch butterflies - He, Elise (PeerJ, 2020)
BACKGROUND: Oviposition decisions are critical to the fitness of herbivorous insects and are often impacted by the availability and condition of host plants. Monarch butterflies (Danaus plexippus) rely on milkweeds (Asclepias spp.) for egg-laying and as food for larvae. Previous work has shown that monarchs prefer to oviposit on recently regrown plant tissues (after removal of above-ground biomass) while larvae grow poorly on plants previously damaged by insects. We hypothesized that these effects may depend on the life-history strategy of plants, as clonal and non-clonal milkweed species differ in resource allocation and defense strategies. METHODOLOGY/PRINCIPAL FINDINGS: We first confirmed butterfly preference for regrown tissue in a field survey of paired mowed and unmowed plots of the common milkweed A. syriaca. We then experimentally studied the effects of plant damage (comparing undamaged controls to plants clipped and regrown, or damaged by insects) on oviposition choice, larval performance, and leaf quality of two closely related clonal and non-clonal species pairs: (1) A. syriaca and A. tuberosa, and (2) A. verticillata and A. incarnata. Clonal and non-clonal species displayed different responses to plant damage, impacting the proportions of eggs laid on plants. Clonal species had similar mean proportions of eggs on regrown and control plants (≈35–40% each), but fewer on insect-damaged plants (≈20%). Meanwhile non-clonal species had similar oviposition on insect-damaged and control plants (20–30% each) but more eggs on regrown plants (40–60%). Trait analyses showed reduced defenses in regrown plants and we found some evidence, although variable, for negative effects of insect damage on subsequent larval performance. CONCLUSIONS/SIGNIFICANCE: Overall, non-clonal species are more susceptible and preferred by monarch butterflies following clipping, while clonal species show tolerance to clipping and induced defense to insect herbivory. These results have implications for monarch conservation strategies that involve milkweed habitat management by mowing. More generally, plant life-history may mediate growth and defense strategies, explaining species-level variation in responses to different types of damage.